2013
DOI: 10.1007/s12519-013-0398-0
|View full text |Cite
|
Sign up to set email alerts
|

The differences in T and B cell subsets in thyroid of children with Graves’ disease and Hashimoto’s thyroiditis

Abstract: Graves' disease is characterized by the increased number of CD4+ T cells and CD8+ T cells. Hashimoto's thyroiditis is characterized by the low number of CD4+ T cells and increased number of CD8+ T cells. CD8+ T cells have cytotoxic properties only in Hashimoto's thyroiditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
5

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
0
29
0
5
Order By: Relevance
“…In their study Beń-Skowronek et al [ 16 ] found an increased number of plasma cells in HT. CD79 alpha+ B cells constituted almost half of the cells in the mononuclear lymphatic infiltrates; in HT, foci of destruction of thyroid follicles and thyrocytes were visible at the sites of accumulation of plasma cells.…”
Section: B Lymphocytesmentioning
confidence: 96%
See 1 more Smart Citation
“…In their study Beń-Skowronek et al [ 16 ] found an increased number of plasma cells in HT. CD79 alpha+ B cells constituted almost half of the cells in the mononuclear lymphatic infiltrates; in HT, foci of destruction of thyroid follicles and thyrocytes were visible at the sites of accumulation of plasma cells.…”
Section: B Lymphocytesmentioning
confidence: 96%
“…Observations under a light microscope revealed that T suppressor/cytotoxic cells were accumulated at the sites of destruction of thyroid follicles. These sites were surrounded by connective tissue fibers and fibroblasts [ 16 ].…”
Section: T Lymphocytesmentioning
confidence: 99%
“…Actually, the pathogenic factors in Graves' hyperthyroidism are the autoaggressive CD4 + cells which drive the maturation of the plasma cells and secretion of stimulatory autoantibody targeting thyrotrophin (TSH) receptor (i.e., TR-Ab). In hypothyroid HT, however, the downregulated or even inverted CD4/CD8 ratio results from increased frequency of CD8 + cells, whose infiltration and cytolytic effects could be directly responsible for the destruction of the follicular thyroid and thyrocytes [ 23 ]. Thus, the divergence of T cell polarization may exactly explain for the main reason for the completely opposite clinical manifestations in GD and HT.…”
Section: Discussionmentioning
confidence: 99%
“…HT, also referred to as chronic lymphocytic thyroiditis, is an autoimmune disease in which the thyroid gland is attacked by a variety of cell- and antibody-mediated immune processes [ 32 ]. A decrease in the CD4/CD8 ratio in HT hypothyroid patients was observed [ 23 ], in contrast to an increase in the ratio in autoimmune hyperthyroid patients. This suggests a different role for T lymphocytes in the pathogenesis of the two major human autoimmune thyroid diseases [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antithyroid inflammatory reaction in HT is enhanced by several mechanisms, counting on the participation of autoreactive CD4 + T cells, CD8 + cytotoxic T cells and anti-thyroid antibodies producing-B cells. An influx of the lymphoid cells, dendritic cells and macrophages into thyroid occurs as a consequence of inflammatory events (Antonelli A, 2015;Ben-Skowronek, 2013). The disease is a result of a Th1 immune response which triggers cell mediated immunity and thyroid follicular cell death by apoptosis.…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%